A new automated compact substation for distribution system in Malaysia - Ahmed, Musse Mohamud (2010)
This project has developed a new distribution automation system and remote metering system. It is a customized distribution automation system (DAS) for secure fault isolation at the low voltage (LV) downstream, 415/240V by using the Tenaga Nasional Berhad (TNB) distribution system. It is the first DAS research work done on customer side substation for operating and controlling between the consumer side system and the substation in an automated manner. Most of the work is focused on developing very secure fault isolation whereby the fault is detected, identified, isolated and cleared in few seconds. Supervisory Control and Data Acquisition (SCADA) techniques has been utilized to build Human Machine Interface (HMI) that provides a graphical operator interface functions to monitor and control the system. Microprocessor based Remote Monitoring Devices have been used for customized software to be downloaded to the hardware. Power Line Carrier (PLC) has been used as communication media between the consumer and the substation. As result, complete DAS fault isolation system has been developed for cost reduction, maintenance time saving and less human intervention during faults. This research has developed Automated Meter Reading (AMR) system in addition to DAS.